Borgerinddragelse som opdragelse til repræsentativt demokrati - Böss Michael (Politik, 2015)
The purpose of the article is to discuss whether decreasing con dence in politicians, political parties and governments and falling electoral participation should be seen as expressions of a crisis of representative democracy. Although it does point out elements that re ect a disjunction between the classical argument for representative democracy – legitimacy and e ectiveness – the article rejects this perception. e article argues, however, that there are good reasons for supplementing representative democracy with deliberative processes as a means of keeping a democratic culture vibrant and enhancing the public’s understanding of the character, aims, and conditions of representative democracy.